Numerical simulation and design recommendations for prestressed steel stayed columns subjected to static and dynamic effects - Aya AboElnaga; Mohamed Mortagi; Mohamed E. El Madawy; M. Naguib; A. H. A. Abdelrahman (Scientific Reports)
Abstract This study investigates the static and dynamic behavior of prestressed steel stayed columns (PSCs), with a particular emphasis on buckling performance under both axial and seismic loading conditions. Unlike prior work that primarily focused on static response or simplified configurations, this research offers a comprehensive investigation encompassing modal analysis and time-history response under seismic excitation, providing valuable insights into the dynamic performance of PSC systems. Advanced finite element (FE) models are developed in ABAQUS using fully automated scripting that defines node coordinates and element connectivity for main columns, cross-arms, and cable stays. These models incorporate geometric and material nonlinearities and are validated against existing experimental and analytical results. A novel design configuration featuring two-level cross-arms is introduced, substantially expanding beyond the conventional single-level systems addressed in earlier studies. Through an extensive parametric study, key parameters such as cross-arm length, cable diameter, and geometric proportions are systematically examined. Based on the numerical findings, new predictive formulas are proposed to estimate the ultimate buckling capacity of two-level PSCs, supporting efficient and resilient preliminary design.